2011
DOI: 10.1167/iovs.11-7516
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of α1-Adrenoceptor Subtypes in Murine Ophthalmic Arteries

Abstract: These findings provide evidence that the α(1A)-AR subtype mediates adrenergic vasoconstriction in murine ophthalmic arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Using real‐time PCR, we recently demonstrated that murine ophthalmic arteries expressed mRNA for all three α 1 ‐adrenoceptor subtypes at similar levels (Gericke et al ., ). In the present study, we conducted analogous studies in isolated retinal arterioles with intact endothelium pooled from seven wild‐type mice of the same genetic background as those used in the previous study.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Using real‐time PCR, we recently demonstrated that murine ophthalmic arteries expressed mRNA for all three α 1 ‐adrenoceptor subtypes at similar levels (Gericke et al ., ). In the present study, we conducted analogous studies in isolated retinal arterioles with intact endothelium pooled from seven wild‐type mice of the same genetic background as those used in the previous study.…”
Section: Resultsmentioning
confidence: 98%
“…Several previous studies on mRNA and protein expression reported that the mRNA expression levels of individual α 1 ‐adrenoceptor subtypes were in fairly good agreement with their protein levels or their contribution to adrenergic vasoconstrictor responses (Rudner et al ., ; Hosoda et al ., ; Marti et al ., ; Jensen et al ., ). Other studies, including our own in murine ophthalmic arteries (Gericke et al ., ), however, demonstrated that the presence of mRNA or even protein of a particular α 1 ‐adrenoceptor subtype does not necessarily indicate the participation of that receptor subtype in vasoconstriction (Piascik et al ., ; Yang et al ., 1997; 1998; Hrometz et al ., ). The results of the present study represent another example of discrepancy between mRNA expression and the particular functional role of α 1 ‐adrenoceptor subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pharmacologic action of PE is mediated by a-adrenoreceptors and their activation will tend to lower IOP through the reduction of aqueous humor production by its action on the ciliary body 42 and also through its vasoconstrictive action on the ophthalmic arteries owing to the artery's rich sympathetic innervation. 43,44 The nonselective activation of a 2 selective adrenergic receptor by PE may also have the effect of lowering IOP, similar to the action of the selective a 2 adrenergic agonists such as apraclonidine by decreasing aqueous production. 45,46 In effect, the stimulation of arterial hypertension by PE in our study is analogous to the sympathoadrenal activation of arterial hypertension observed during the stress response 47 as well as during isometric exercises.…”
Section: Discussionmentioning
confidence: 99%